Coenzyme Q10 supplementation in patients with heart failure: A literature review (Research, Society and Development, 2026)
Coenzyme Q10 (CoQ10), an antioxidant present in foods and synthesized endogenously, has been studied for its benefits on cardiac function. However, further research is needed to validate its recommendation as a non-pharmacological treatment for heart failure (HF). This study aims to conduct a narrative review of the literature from 2018 to 2024, regarding the use of CoQ10 as a supplement for patients with heart failure. A total of 236 articles were initially found, including clinical trials, single-center, and empirical studies on CoQ10 supplementation in HF, while duplicate and unrelated articles were excluded. After screening, four studies were selected for analysis. CoQ10 supplementation ranged from 300 mg/day (100 mg three times daily), 300 mg/day (single dose), up to 600 mg/day, with intervention periods ranging from 30 days to 2 years. Studies using a single daily dose ≥300 mg/day showed more evident benefits, indicating an increase in left ventricular ejection fraction (LVEF) and a reduction in NT-proBNP, improvements in the 6-minute walk test (6MWT), changes in the New York Heart Association (NYHA) functional classification, and a decrease in major adverse cardiovascular events (MACE) in the supplemented groups. Therefore, CoQ10 may be effective as a complementary therapy, helping to improve cardiac function and reduce adverse clinical outcomes in patients with heart failure. However, further studies are needed to consolidate scientific evidence and guide future recommendations in clinical guidelines.